Determinants of public transport use in Perth, Western Australia - Nau, S Zaung (Curtin University, 2015)
This study examines the primary determinants explaining spatial and temporal variations in public transportation use in Perth using 2009 SmartRider data. The developed robust predictive model includes land use, urban form, socio-economic characteristics and public transport availability. Land-use development integrated with sustainable transportation systems, more frequent and densely distributed feeder bus service to train stations, density of low-income resident and university student populations are highlighted as important for policy making encouraging increased public transport use.